Mathematical modeling training of future metallurgical engineers in the process of professionally oriented problems solution - Горшкова, Ганна Алімівна (Pedagogy of Higher and Secondary Education, 2015)
Gorshkova H. A. Mathematical modeling training of future metallurgical engineers in the process of professionally oriented problems solution. This article examines the possibility of using mathematical modeling in the process of future metallurgical engineers training. It was emphasized that the introduction of new technologies in the development and operation of the metallurgical complex significantly increases the demands in the field of basic sciences for university graduates of engineering profile.